A STUDY OF RULES AND REGULATIONS FOR AIRSIDE VEHICLE DRIVING-VIOLATION BEHAVIORS AT SUVARNABHUMI AIRPORT - Pattavee, Prapakorn; Temkaew, Waraporn; Khamphoh, Thanyarat (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
The objective of this independent study is 1) to examine human behaviors that violate the rules and regulations for airside driving at Suvarnabhumi airport. And 2) to find direction for improvement and adjustment on violations of rules and regulations for airside driving at Suvarnabhumi airport by studying 17 informative operators’ interviewees who operate their duties in the airside area. And also collecting the data from the rules and regulations for airside driving at Suvarnabhumi airport textbook, to analyze the concept and theory of the accident, human factor ideas about human behavior involved in rules and regulations for airside driving at Suvarnabhumi airport violation, and descriptive lecture in accordance with the goals of independent study. The result of the study revealed that human behavior that violates the rules and regulations for airside driving at Suvarnabhumi airport is caused by human mistakes. The frequent violation is the habit of operators who accept the risk of driving beyond the speed limit. The second type of violation was caused by immediate events between drivers and their working environment.